Praise in the Poetry of Andalusian Poetesses: (91ـ897هـ/ 711ـ 1492م) - Mahmir, Ruqaya; Bouali, Abdulrahman; Jarrar, Salah (Al-Adab Journal, 2023)
Praise is an ancient poetic subject that appeared in pre-Islamic poetry, and in the poetic works of all ages until today. Most of the famous panegyrics were composed by men, this does not mean that this subject was restricted to men rather than women, but we have received poems of praise written by women of great magnificence and ingenuity at different ages. Indicating the motives behind it.